The Role of the Police in Combating the Crime of Theft with Violence within the Jurisdiction of the Aceh Tenggara Resort Police - Abdi Ridho; Abdul Rahman Maulana Siregar; Ismaidar Ismaidar (Utan Kayu Publishing, 2025)
This study aims to analyze the role of the Police in addressing violent theft crimes and the obstacles faced by the Aceh Tenggara Police Resort. The research uses an empirical method with a qualitative descriptive approach. Data were obtained through observation, interviews with police personnel, and documentation related to crime prevention efforts. Data analysis was conducted by examining the roles, strategies, and challenges faced in the implementation of police duties. The results show that the role of the Aceh Tenggara Police Resort is carried out in an integrated manner through preemptive, preventive, and repressive efforts, including legal guidance and public awareness programs, routine patrols in high-risk areas, and law enforcement from investigation to prosecution. The support of Bhabinkamtibmas and active community cooperation enhances the effectiveness of prevention and case resolution, thereby maintaining public security and order. The obstacles faced include limited personnel and infrastructure, difficult-to-access geographical conditions, and technical investigation challenges, such as insufficient evidence and uncooperative witnesses. To overcome these challenges, the Aceh Tenggara Police Resort optimizes investigation management, personnel assignment, cross-functional coordination, persuasive approaches, technology utilization, and regular evaluation of investigations